Enterobius vermicularis in anterior chamber of eye - Bajracharya, Kabindra; Bhari, Arjun Malla; Rai, Salma KC; Pandey, Saraswati (Asian Journal of Medical Sciences, 2019)
Enterobius vermiculari which is often referred as pinworm, is an intestinal nematode which is transmitted through fecal-oral route. The extraintestinal presentation of the worm is rare. A live worm, Enterobius vermicularis in anterior chamber is a very rare case. To present an unusual case of Enterobius vermicularis in anterior chamber of right eye in a 3 years old girl. Visual acuity assessment, slit lamp examination and ultrasonography of the eye were performed. The worm was found in anterior chamber of right eye at 8-9 o' clock hour position, coiling at the presentation. The living, white worm was freely moving and changing position frequently. There was hypopyon with exudates inferiorly. The pupil was irregular, posterior synechiae was present with cataractous lens. The living worm was removed surgically under general anesthesia and sent for microbiological examination. Synecholysis with lens aspiration and Posterior chamber intraocular lens implantation was done in second surgery. An adult worm in anterior chamber is rare. Treatment is surgical removal. The visual prognosis is not good when the case present with severe form of anterior uveitis and complicated cataract.